Students’ Difficulties in Mastering Vocabulary in Eighth Graders at SMPN 06 Kaur - Hernandes, Febra; Rizal, Syamsul; Martina, Feny (Jurnal Bahastra, 2025)
This study investigates the challenges faced by eighth-grade students at SMPN 06 Kaur in mastering English vocabulary, with a particular focus on identifying underlying factors that contribute to their difficulties. Employing a quantitative descriptive method, the research involved distributing a 25-item questionnaire to one class. Responses were analyzed using SPSS 26 to assess the students’ vocabulary comprehension. The findings reveal that, among 30 respondents, only a few achieved a score of 84—classified as “very good”—while the majority scored between 70 and 74, indicating a generally “good” level of vocabulary mastery. Despite this, the average frequency score across categories remained low, with only 1% of students reaching the maximum score. The data suggest that while most students possess a satisfactory understanding of English vocabulary, a subset continues to struggle, particularly with grammar and pronunciation. These challenges underscore the need for targeted pedagogical strategies that address specific linguistic weaknesses to enhance overall language proficiency.